The influence of due professional care, competency, time budget pressure, and work experience on audit quality (study of auditors working at Kap Semarang) - Suratman; Linda Novasari (Institute of Computer Science (IOCS), 2023)
This research was conducted to empirically prove the effect of Due Professional Care, Competence, Time Budget Pressure, and Work Experience on audit quality. The number of samples used in this study was 103 auditors from 18 Public Accounting Firms in Semarang City. Sampling in this study was carried out using the Incidental sampling technique or often called convenience sampling, and this research is included in the non-probability sampling. The convenience sampling technique is used in this study because the population size is uncertain. This study used quantitative data analysis techniques using SPSS 25 software. Data analysis used multiple linear regression. The results of this study indicate that due professional care has a positive effect on audit quality, competence has a positive effect on audit quality, time budget pressure has a negative effect on audit quality, and work experience does not affect audit quality.